PENGGUNAAN MODEL PEMBELAJARAN MOMBI PADA MATERI ALAT OPTIK DI SMP KATOLIK HATI KUDUS KEROIT - Nelwan, Yulio Nelson; Umboh, Sixtus Iwan; Mongan, Satyano (Charm Sains: Jurnal Pendidikan Fisika, 2024)
Learning strategies by utilizing appropriate learning models will affect student learning outcomes. Many new learning models that can be accessed in various sources are alternatives to choose from in improving student learning outcomes. This study aims to determine the use of the Mombi model in teaching convex lens material in junior high school. This research is a pre-experimental study with a one group pretest-posttest design. The research subjects were students of class VIII at Hati Kudus Keroit Catholic Middle School, South Minahasa in the 2022/2023 academic year. Data collection uses tests with test instruments in the form of essays and science process skills. The results of the study concluded that the average pretest result was 24.05 and the posttest result was 83.33. The average results of the science process skills assessment are in very good criteria (80% -100%). The results of the t test show that the hypothesis is accepted which states that the use of the Mombi model has an effect on increasing student learning outcomes